The UCR Minicore: a resource for cowpea research and breeding. Issue 3 (6th May 2021) - Muñoz‐Amatriaín, María; Lo, Sassoum; Herniter, Ira A.; Boukar, Ousmane; Fatokun, Christian; Carvalho, Márcia; Castro, Isaura; Guo, Yi‐Ning; Huynh, Bao‐Lam; Roberts, Philip A.; Carnide, Valdemar; Close, Timothy J.
Abstract: Incorporation of new sources of genetic diversity into plant breeding programs is crucial for continuing to improve yield and quality, as well as tolerance to abiotic and biotic stresses. A minicore (the "University of California, Riverside (UCR) Minicore") composed of 368 worldwide accessions of cultivated cowpea has been assembled, having been derived from the UCR cowpea collection. High‐density genotyping with 51, 128 SNPs followed by principal component and genetic assignment analyses identified six subpopulations in the UCR Minicore, mainly differentiated by cultivar group and geographic origin. All six subpopulations were present to some extent in West African material, suggesting that West Africa is a center of diversity for cultivated cowpea. Additionally, population structure analyses supported two routes of introduction of cowpea into the U.S.: (1) from Spain to the southwest U.S. through Northern Mexico and (2) from Africa to the southeast U.S. via the Caribbean. Genome‐wide association studies (GWAS) narrowed several traits to regions containing strong candidate genes. For example, orthologs of the Arabidopsis FLOWERING LOCUS T lie within a major QTL for flowering time. In summary, this diverse, yet compact cowpea collection constitutes a suitable resource to identify loci controlling complex traits, consequently providing markers to assist with breeding to improve this crop of high relevance to global food and nutritional security.